Identifying the source region of plasmaspheric hiss. Issue 9 (13th May 2015) - Laakso, Harri; Santolik, Ondrej; Horne, Richard; Kolmasová, Ivana; Escoubet, Philippe; Masson, Arnaud; Taylor, Matthew
Abstract The presence of the plasmaspheric hiss emission around the Earth has been known for more than 50 years, but its origin has remained unknown in terms of source location and mechanism. The hiss, made of whistler mode waves, exists for most of the time in the plasmasphere and is believed to control the radiation belt surrounding the Earth which makes its understanding very important. This paper presents direct observational evidence that the plasmaspheric hiss originates in the equatorial region of the plasmaspheric drainage plumes. It shows that the emissions propagate along the magnetic field lines and away from the equator in the plumes but toward the equator at lower L shells inside the plasmasphere. The observations also suggest that the hiss waves inside the plasmasphere are absorbed as they cross the equator.